Pengamanan Basis Data Kasus Kekerasan pada Perempuan dan Anak Menggunakan Algoritma Vigenere Cipher dan Base64 - Oktaviany, Fenny Fitria; Ardhianto, Eka (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Cases of violence against children and women that occur in Indonesia are still a serious problem that must be addressed immediately. The official website of the Ministry of Women's Empowerment and Child Protection shows that in the last 3 years these cases have increased significantly. One of the efforts that have been made is to form Integrated Service Centers that spread across various cities as a forum for complaints. The complaint data must be secured to prevent misuse by unauthorized parties. The purpose of this study is to secure these data using the Vigenere Cipher and Base64 algorithms and a combination of the two algorithms. The entropy value is used as a test performance metric for each algorithm. From this test, the level of information security obtained was 72.77% on data encrypted using a combination of the Base64 and Vigenere Cipher algorithms